Pengaruh Kepemimpinan Instruksional Kepala Sekolah dan Budaya Sekolah Terhadap Disiplin Kerja Guru SD Negeri di Kecamatan Pedurungan Kota Semarang - Lasminto Lasminto; Nur Khoiri; Lilik Ariyanto (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: The purpose of this study is to determine and analyze the influence of principal leadership and work culture on the work discipline of elementary school teachers in Tembalang District, Semarang City. This study uses quantitative methods. The population in this study was 382 teachers with proportional random sampling techniques to 195 elementary school teachers in Tembalang District, Semarang City. Data collection techniques used observation, questionnaires and documentation methods. Data analysis techniques used classical assumption tests, namely normality tests, linearity tests, multicollinearity tests, heteroscedasticity tests, multiple linear analysis, T-test (Partial), F-test (Simultaneous) and coefficient of determination (r2) tests. The results of the first test are a positive and significant influence of principal leadership on the work discipline of elementary school teachers in Tembalang District, Semarang City. The results of the second test are a positive and significant influence of work culture on the work discipline of elementary school teachers in Tembalang District, Semarang City. The results of the third test are a positive and significant influence of principal leadership and work culture simultaneously on the performance of elementary school teachers in Tembalang District, Semarang City. Keywords: Instructional Leadership; Work Culture; Work Discipline. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis pengaruh kepemimpinan kepala sekolah dan budaya kerja terhadap disiplin kerja guru SD Negeri se-Kecamatan Tembalang Kota Semarang. Penelitian ini menggunakan metode kuantitatif. Populasi dalam penelitian ini adalah 382 guru dengan teknik proportional random sampling menjadi 195 guru sd negeri se-kecamatan Tembalang kota Semarang. Teknik pengumpulan data menggunakan metode observasi, kuesioner dan dokumentasi. Teknik analisis data menggunakan uji asumsi klasik yaitu uji normalitas, uji liniearitas, uji multikolinearitas, uji heterokedastisitas, analisis linear berganda, uji T (Parsial), uji F (Simultan) serta uji koefisien determinasi (r2). Hasil pengujian pertama adalah adanya pengaruh positif dan signifikan kepemimpinan kepala sekolah terhadap disiplin kerja guru SD Negeri se-Kecamatan Tembalang Kota Semarang. Hasil pengujian kedua adalah adanya pengaruh positif dan signifikan budaya kerja terhadap disiplin kerja guru SD Negeri se-Kecamatan Tembalang Kota Semarang. Hasil pengujian ketiga adalah adanya pengaruh positif dan signifikan kepemimpinan kepala sekolah dan budaya kerja secara simultan terhadap kinerja guru SD Negeri se-Kecamatan Tembalang Kota Semarang. Kata kunci: Kepemimpinan Intruksional; Budaya Kerja ; Disiplin Kerja